Molecular genetics of head and neck squamous cell carcinoma. Issue 3 (May 2019) - Saada-Bouzid, Esma; Peyrade, Frederic; Guigay, Joël
Abstract : Purpose of review: The aim of this review is to summarize the current knowledge on the genomic characterization of squamous cell carcinomas of the head and neck (HNSCC) and discusses how these abnormalities could be incorporated into a therapeutic approach. Recent findings: Tobacco and HPV infection, the two main risk factors of HNSCC, allow the definition of two groups with distinct anatomoclinical and genetic features. As tobacco and HPV infection are not exclusive, exposure to both risk factors is associated with an intermediate prognostic. HPV-positive, nontobacco-related HNSCCs are associated with a better prognosis, a rather more simple genomic profile, frequent activating mutations of genes involved in pi3kinase pathway, and the very low incidence of mutations of tumor suppressor genes. HPV-negative, tobacco-related HNSCC are genetically more complex. HPV-negative HNSCC are characterized by almost mandatory inactivating mutations/deletions of tumor suppressor genes (especially TP53 and CDKN2A ) and the occurrence, though less frequent, of activating mutations or amplifications of some oncogenes that encode for cell cycle proteins or receptors with tyrosine kinase activity. Despite many efforts to improve therapeutic targeting in RM HNSCC, Cetuximab, a monoclonal antibody targeting REGF, remains the sole approved targeted treatment in RM HNSCC. Summary: Despite the increasingly precise genomic characterization of HNSCCs, precision medicine is struggling to find its place in the management of HNSCCs. Inclusion of enriched populations in dedicated trials is likely to help implement precision medicine in the management of HNSCCs.